1983
DOI: 10.1111/j.1440-6055.1983.tb01872.x
|View full text |Cite
|
Sign up to set email alerts
|

ABUNDANCE AND MORTALITY OF OVERWINTERING HELIOTHIS SPP.

Abstract: Field surveys, field cage studies, and records of light trap catches were used to follow the abundance and mortality of Heliofhis puncfiger (Wallengren) and H . armiger (Hiibner), through the autumn, winter and spring. over a 9 year period.Both the timing of spring emergence and magnitude of moth flights of H . armiger were consistent with prior observations of autumn and winter populations in the Namoi Valley. Subsequent abundance was greater in 2 seasons when wheat anthesis and spring emergence coincided. bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
55
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 9 publications
7
55
0
Order By: Relevance
“…promissorius oviposits in pupae (Murray unpubl. data Room (1979) and Wilson (1983) recorded I. promissorius in larval collections in the Namoi Valley but gave no indication of its relative abundance. As expected, I. protnissorius was common in samples of overwintering H. arniigera pupae in the Narnoi Valley (Fitt and Daly 1990 (McDougall 1934;Goodyer 1983;Forrester et al 1984), they are also reported as predators of pest insects in pasture (Robertson et al 1981;Robertson 1987).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…promissorius oviposits in pupae (Murray unpubl. data Room (1979) and Wilson (1983) recorded I. promissorius in larval collections in the Namoi Valley but gave no indication of its relative abundance. As expected, I. protnissorius was common in samples of overwintering H. arniigera pupae in the Narnoi Valley (Fitt and Daly 1990 (McDougall 1934;Goodyer 1983;Forrester et al 1984), they are also reported as predators of pest insects in pasture (Robertson et al 1981;Robertson 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, such studies can be used to indicate the contribution of different crops to the carryover of pyrethroid resistance from one season to the next (Daly and Fitt 1990). Because of the relatively low occurrence of overwintering populations of H. punctigera in agricultural regions (Wilson 1983;Learmonth 1986;Fitt and Daly 1990), investigations should examine H . punctigera in more detail in other regions where winter breeding is known to occur (Gregg et al 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is especially so in irrigated crops where most pupae are located in ridges (Wilson 1983). In raingrown crops ridging is less developed and waterlogging may have greater influence.…”
mentioning
confidence: 99%